In this section we will obtain the expressions for the differentials dH, dA, dG using the relation $dU=TdS-PdV$ from the definitions $H=U+PV$, $A=U-TS$ and $G=H- TS$.

We start by getting dH: \begin{equation} dH=d(U+PV)=dU+PdV+VdP=TdS-PdV+PdV+VdP=TdS+VdP \end{equation} Similarly we get dA and dG. \begin{equation} dA=d(U-TS)=dU-SdT-TdS=\cancel{TdS}-PdV-SdT-\cancel{TdS}=-SdT-PdV \end{equation} \begin{equation} dG=d(H-TS)=dH-TdS-SdT=\cancel{TdS}+VdP-\cancel{TdS}-SdT=-SdT+VdP \end{equation} Therefore the Gibbs equations are: \begin{eqnarray} dU & = & TdS - PdV\\ dH & = & TdS+VdP\\ dA & = & -SdT-PdV\\ dG & = & -SdT+VdP \end{eqnarray}

From equation (29) the following relations can be obtained: \begin{equation} \left(\frac{\partial U}{\partial S}\right)_v=T\;\;\; \left(\frac{\partial U}{\partial V}\right)_s=-P \end{equation} The first relation is obtained by making dV=0 in (29), and the second with dS=0.

From equation (30) we obtain: \begin{equation} \left(\frac{\partial H}{\partial S}\right)_p = T\;\;\; \left(\frac{\partial H}{\partial P}\right)_s = V \end{equation} From equation (31) we obtain: \begin{equation} \left(\frac{\partial A} {\partial T}\right)_v = -S\;\;\; \left(\frac{\partial A}{\partial V}\right)_T = -P \end{equation} From equation (32) we obtain: \begin{equation} \left(\frac{\partial G }{\partial T}\right)_p = -S\;\;\; \left(\frac{\partial A}{\partial P}\right)_T = V \end{equation} The objective of these equations is to relate thermodynamic properties that are difficult to obtain with others that are easily measurable, such as: $C_p$, $\alpha$ and $\kappa$.

We use cookies

We use cookies on our website. Some of them are essential for the operation of the site, while others help us to improve this site and the user experience (tracking cookies). You can decide for yourself whether you want to allow cookies or not. Please note that if you reject them, you may not be able to use all the functionalities of the site.